Regulation of Rubisco activity and diurnal changes of photosynthetic rate in rice by ecology factors - WENG Xiao-yan; JIANG De-an (浙江大学学报. 农业与生命科学版, 2002)
The rice cultivar Zhenong 952 grown in pots were used to determine the diurnal changes of photosynthetic rate (Pn) and its major affecting factors, i.e. photosynthetic photon flux (PPF), relative humidity (RH）, temperature (T）, CO2 concentration, stomatal conductance (Sc) and Rubisco activity. The relation between photosynthetic rate and its factors were analysed by the regression analysis. Stomatal conductance are physiological factors which affect photosynthetic rate. Photosynthetic photon flux and relative humidity are major ecology factors which affect photosynthetic rate by Rubisco activity.